Microbiome Response to Hot Water Treatment and Potential Synergy With Biological Control on Stored Apples - Wassermann, Birgit; Kusstatscher, Peter; Berg, Gabriele (Frontiers in Microbiology, 2019)
Postharvest food decay is one major issue for today’s food loss along the supply chain. Hot water treatment (HWT), a sustainable method to reduce pathogen-induced postharvest fruit decay, has been proven to be effective on a variety of crops. However, the microbiome response to HWT is still unknown, and the role of postharvest microbiota for fruit quality is largely unexplored. To study both, we applied a combined approach of metabarcoding analysis and real time qPCR for microbiome tracking. Overall, HWT was highly effective in reducing rot symptoms on apples at industrial scale. The efficiency was rather due to induced plant response than due to alterations of the microbiome; the fungal microbiota was only slightly, and the bacterial community insignificantly affected. Pathogen infection, however, significantly decreased the bacterial and fungal diversity, and especially rare taxa were almost eradicated in diseased apples. Here, almost 90% of the total fungal community was composed by co-occurring storage pathogens Neofabraea alba and Penicillium expansum. Additionally, the prokaryote to eukaryote ratio, almost balanced in apples before storage, was shifted to 0.6% bacteria and 99.4% fungi in diseased apples, albeit the total bacterial abundance was stable across all samples. Healthy stored apples shared 18 bacterial and four fungal taxa that were not found in diseased apples, therefore defining a health-related postharvest microbiome. In addition, applying a combined approach of HWT and a biological control consortium consisting of Pantoea vagans 14E4, Bacillus amyloliquefaciens 14C9 and Pseudomonas paralactis 6F3, were proven to be efficient in reducing both postharvest pathogens. Our results provide first insights into the microbiome response to HWT, and suggest a combined treatment with biological control agents.